Evaluation of the community based group parenting intervention ‘Getting through the day’ - Bland, Kirsten (The University of Edinburgh, 2010)
Childhood behavioural disorders affect up to 9% of UK children under the age of ten (Meltzer et al.,2000). The consequences of these difficulties are widespread, placing the dchild at greater risk for later psychopathology, unemployment, relatioship problems and criminal activity. The trajectory towards the development of behavioural difficulties presents a complex milieu of potential risk and protective factors. Individual risk factors includes cognitive deficits, premature birth and childhood physical illness, although these are tempered by interactions with environmental risk factors such as low socioeconomic status and parental factors such as parental self-efficacy and mental health. Parenting skills are consistently highlighted as a key factor for the mediation of behavioral difficulties, and consequently lend themselves to the most influential intervention approach - the group parenting programme. Despite a wealth of programmes available, strenth of content and supporting evidence base vary widely. Current approaches are outlined and critiqued. 'Getting throught the day' is a manualised group parenting programme developed to impact upon child behaviour, parental self-efficacy and parental wellbeing. The aim of the current study was to evaluate this resource in the community setting within which it is delivered. Following longitudinal design, group participants and parents of 'healthy controls' from local schools and nurseries completed the standarised assessment questionnaires Strenght and Difficulties Questionnaire (corroborated by teacher version), Parenting Stress Index-Short Form, Hospital Anxiety and Depression Scale and the non-standardised Tool to Measure Parenting Self-Efficacy. statistical analyses of Analysis of Variance and Analysis of Covariance were conducted as appropriate, Results indicate positive change for intervention group participants as compared to healthy controls across domains of parent self-efficacy and parent mental health. Results and clinical implications are discussed in the context of this valuable resource and the existing evidence base for group parenting interventions.
Keywords: childhood behavioural disorders; parenting skills; group parenting interventions